2009
DOI: 10.1161/strokeaha.108.538058
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Intracranial Aneurysms in Patients With Internal Carotid Artery Stenosis

Abstract: Background and Purpose-Smoking and hypertension are important risk factors for atherosclerotic carotid artery disease, but also for intracranial aneurysms. We studied the presence of aneurysms in a series of patients with internal carotid artery (ICA) stenosis and performed a systematic review of the literature to assess in patients with ICA stenosis the prevalence of intracranial aneurysms, gender differences in prevalence, and the size of the aneurysms found. Methods-In a prospectively collected series of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 23 publications
3
33
1
Order By: Relevance
“…Nevertheless, female patients had a higher coexistence of CA in our patients with BI or BH. A higher prevalence of CA also refers to female patients with ICA stenosis [10] and women in general populations [17,19,20]. Therefore, the female predominance of incidental CA could contribute to female hormonal factors rather than the atherosclerotic profile, such as smoking and hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, female patients had a higher coexistence of CA in our patients with BI or BH. A higher prevalence of CA also refers to female patients with ICA stenosis [10] and women in general populations [17,19,20]. Therefore, the female predominance of incidental CA could contribute to female hormonal factors rather than the atherosclerotic profile, such as smoking and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral aneurysms (CA) are incidentally detected when brain MRA is performed in asymptomatic healthy volunteers [6,7]. Prevalence of incidental CA varies among atherosclerotic patients, including those with angina pectoris, ischemic cerebrovascular disease, and internal carotid artery (ICA) stenosis [8][9][10]. A systematic review of autopsy and angiography studies suggests that atherosclerotic diseases seem to increase the risk of incidental CA [11].…”
Section: Introductionmentioning
confidence: 99%
“…UIAs are incidentally found when a brain MRA is performed in asymptomatic healthy volunteers 6,7 ; UIAs in stroke patients are also incidentally detected 2,5,6,[8][9][10] . Some previous studies indicated that cerebrovascular diseases seem to increase the occurrence of UIAs 5,11 .…”
mentioning
confidence: 99%
“…35 In addition, a recent metaanalysis indicates that the overall prevalence of intracranial aneurysms in patients with internal carotid artery stenosis (3.2%) is higher than the reported prevalence of UIAs in the general population. 36 Moreover, a systematic review of autopsy and angiography studies suggests that atherosclerotic diseases Figure 2 Forest plot of symptomatic intracranial hemorrhage rates across case series reporting the safety of IV thrombolysis in acute ischemic stroke patients harboring unruptured intracranial aneurysms CI 5 confidence interval.…”
Section: For the Qualitative Interpretation Of Heterogeneity Imentioning
confidence: 99%